2013
DOI: 10.14236/ewic/hci2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Less is More: Classifying Mobile Interactions to Support Context Sensing in Journeys

Abstract: This paper develops a classification of mobile interactions based on contextual information relevant to the mobile device user in journeys. Context-aware systems can be used to reduce the stress involved, support users in their activities and increase utility of travel time. But context is often portrayed as real, stable and structured, which can limit the value of applications as they lack dynamics and relevancy. This paper aims to classify mobile interactions in journeys by adopting an alternative view of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In addition, our study also echoes the literature on interruptions that has found an impact on our attentional orientation [15,25]. We saw several instances in which members responded to notifications; such a 'readiness to respond' may perhaps be related to the informal nature of the setting in which we conducted our fieldwork [31]. Authors have suggested that although there is a need to be accountable towards collocated members, there is equally a duty to manage accountabilities to those we are remotely connected to [54].…”
Section: Embedding Mobile Devices In Conversationsupporting
confidence: 82%
“…In addition, our study also echoes the literature on interruptions that has found an impact on our attentional orientation [15,25]. We saw several instances in which members responded to notifications; such a 'readiness to respond' may perhaps be related to the informal nature of the setting in which we conducted our fieldwork [31]. Authors have suggested that although there is a need to be accountable towards collocated members, there is equally a duty to manage accountabilities to those we are remotely connected to [54].…”
Section: Embedding Mobile Devices In Conversationsupporting
confidence: 82%
“…Existing HCI studies demonstrate uses of visual representations that partially resemble sales contexts. Visualising granularity resembles research on contextaware applications for travelling people, with having less information, and more accurate information resulting in better design [34]. Adding interactivity enables zooming into more detailed information [66] in demand for less experienced users, without underestimating the experienced ones.…”
Section: Collocated Interactions In the Machine Industrymentioning
confidence: 99%
“…Context is defined by physical locations and objects, social influences, tasks participants aim to do, and how those are interrupted. Equipment and technology, and temporal timebased influences are also involved [31,34]. Using visual representations only once or leaving them behind for extended periods of time is common in selling contexts of the machine industry.…”
Section: Introductionmentioning
confidence: 99%